2010
DOI: 10.1039/c0fo00105h
|View full text |Cite
|
Sign up to set email alerts
|

Tea catechins modulate the glucose transport system in 3T3-L1 adipocytes

Abstract: In this study, we investigated the effects of tea catechins on the translocation of glucose transporter (GLUT) 4 in 3T3-L1 adipocytes. We found that the ethyl acetate fraction of green tea extract, containing abundant catechins, most decreased insulin-induced glucose uptake activity in 3T3-L1 cells. When the cells were treated with 50 μM catechins in the absence or presence of insulin for 30 min, nongallate-type catechins increased glucose uptake activity without insulin, whereas gallate-type catechins decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 31 publications
0
43
0
2
Order By: Relevance
“…This mechanism is similar to the action of insulin and could be attributed to the presence of catechin, which has been isolated from the stem bark of C. pentandra [22]. In fact, Ueda et al [23] showed that catechin induces glucose uptake in 3T3-L1 adipocytes by promoting the translocation of GLUT4 to the plasma membrane. This is likely the mechanism by which the stem bark decoction from C. pentandra increases glucose uptake in the skeletal muscle.…”
Section: Discussionmentioning
confidence: 95%
“…This mechanism is similar to the action of insulin and could be attributed to the presence of catechin, which has been isolated from the stem bark of C. pentandra [22]. In fact, Ueda et al [23] showed that catechin induces glucose uptake in 3T3-L1 adipocytes by promoting the translocation of GLUT4 to the plasma membrane. This is likely the mechanism by which the stem bark decoction from C. pentandra increases glucose uptake in the skeletal muscle.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, we previously reported that catechins, particularly (−)-epigallocatechin-3-gallate, increased glucose uptake and enhanced GLUT4 translocation in L6 myotubes and in the skeletal muscle of rodents in vivo and ex vivo ( 19 ) . In 3T3-L1 cells, non-gallate-type catechins increased glucose uptake and GLUT4 translocation, whereas gallate-type catechins inhibited insulin-stimulated glucose uptake ( 42 ) . Similarly, the intake of green and black tea increased GLUT4 translocation in skeletal muscle and maintained GLUT4 and insulin receptor expression in high-fat diet-fed C57BL/6 mice ( 3 , 21 , 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…2g), such as (−)-epicatechin, 3-O-galloyl-(−)-epicatechin, (−)-epigallocatechin and epigallocatechin 3-gallate (GEGC), are polyphenols present in high concentrations in tea [60]. Green tea and catechins have been demonstrated in cell culture (Table 1), human trials and crosssectional studies ( Table 2) that may reduce adipocyte differentiation and proliferation, lipogenesis [61][62][63], fat mass, body weight, oxidised LDL-c and blood pressure, and can improve glycemic control [64][65][66][67]. GEGC has been widely investigated for its possible body fat-reducing effects.…”
Section: Catechinsmentioning
confidence: 99%
“…Evidences have shown that the anti-adipogenic effects of catechins are mediated by several mechanisms including the inhibition of cell proliferation, a decrease in PPAR-γ and C/EBP-α expression, an increase in glucose uptake [61][62][63], and the induction of thermogenesis via sympathetic nervous system through inhibition of the enzyme catechol-Omethyltransferase as well as noradrenaline enhancement [68]. Moreover, reduced body fat accumulation may also be explained by a decrease in the digestibility of the diet [69,70], higher faecal energy loss, increased post-prandial fat oxidation and a reduction in dietary lipid incorporation into adipose tissue, liver and skeletal muscle [70].…”
Section: Catechinsmentioning
confidence: 99%
See 1 more Smart Citation